2016
DOI: 10.3329/bjms.v15i3.25288
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Contraceptives among Saudi Women in Aseer Region, Saudi Arabia

Abstract: Abstract:Objective: The study was carried out to assess the knowledge, attitude towards, and practice of contraception and the factors that could affect its use among Saudi women in Aseer region of Saudi Arabia. Methods: This cross-sectional and hospital-based study was conducted in Aseer Region, Saudi Arabia, during one year (January, 2014 -December, 2014. Five-hundred women of reproductive age (18-45 year) were interviewed regarding their knowledge, attitude and practices of contraception. The inquiries wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 5 publications
5
17
2
1
Order By: Relevance
“…From the personal domain, knowledge about family planning methods and available health services was discussed as a factor influencing women's SRH [19-21, 25, 26, 28, 30, 32, 33, 35, 39, 43-45, 47-53, 68, 70, 77, 79, 80, 83, 86, 87, 89, 90]. Insufficient knowledge about contraception and lack of basic reproductive knowledge was reported as one of the main barriers to contraception use among Muslim women [20,26,29,31,39,41,46,83,90,91]. Some women are unaware of services available for them [69,74,75,78,87], particularly unmarried women [74,75,78].…”
Section: Theme 1: Insufficient Knowledge and Misconceptions About Conmentioning
confidence: 99%
See 2 more Smart Citations
“…From the personal domain, knowledge about family planning methods and available health services was discussed as a factor influencing women's SRH [19-21, 25, 26, 28, 30, 32, 33, 35, 39, 43-45, 47-53, 68, 70, 77, 79, 80, 83, 86, 87, 89, 90]. Insufficient knowledge about contraception and lack of basic reproductive knowledge was reported as one of the main barriers to contraception use among Muslim women [20,26,29,31,39,41,46,83,90,91]. Some women are unaware of services available for them [69,74,75,78,87], particularly unmarried women [74,75,78].…”
Section: Theme 1: Insufficient Knowledge and Misconceptions About Conmentioning
confidence: 99%
“…On the other hand, many women expressed negative attitudes towards family planning for limiting the number of children [26,32,39,86,88,89]. Some women believed that it would be easier to raise and care for their children if they were closely spaced.…”
Section: Theme 5: Attitudes Towards Family Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of these factors is well documented in other similar studies. 5,9 The current study revealed that only around one-quarter of women had good knowledge about contraception. Most prior studies considered knowing the different contraceptive methods as "knowledge," without assessing women's real understating of contraception, for example, indications/contraindication, side effects, and other uses.…”
Section: Discussionmentioning
confidence: 64%
“…Causes for these findings were determined to be socioeconomic factors, religious beliefs, and lack of proper knowledge and counselling about contraception. [3][4][5] In the UAE, with the tremendous development in various sectors, women are occupying diverse and important positions requiring them to be more productive socially and to have control over their reproduction. Despite the improvement in women's health, the UAE lacks family planning programs and education regarding contraception.…”
mentioning
confidence: 99%